2019
DOI: 10.1177/1179573519843493
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High-Intensity Aerobic Exercise on Cognitive Performance After Stroke: A Pilot Randomised Controlled Trial

Abstract: Background: Aerobic exercise is an effective treatment to improve aerobic capacity following stroke and might also improve cognitive impairments in sub-acute stroke survivors. The aim of the study was to assess the effect of high-intensity aerobic exercise on cognitive impairments in sub-acute stroke survivors. Methods: A pilot, randomised controlled trial on the effects of aerobic exercise on cognitive impairments of stroke patients in the sub-acute (1-3 months) phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 53 publications
2
45
0
1
Order By: Relevance
“…These findings support our second hypothesis that greater improvements in executive functioning will result from HIIT compared to MICE. The results of our study confirm certain results from the literature in children [35], adolescents [33], young adults [37], or the elderly who are healthy [34] or have had a stroke [36]. In addition, our results on the trail making task are consistent with those reported by Pallesen et al who reported an effect of intermittent high intensity training only on the Trail B and not on the Trail A [36].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings support our second hypothesis that greater improvements in executive functioning will result from HIIT compared to MICE. The results of our study confirm certain results from the literature in children [35], adolescents [33], young adults [37], or the elderly who are healthy [34] or have had a stroke [36]. In addition, our results on the trail making task are consistent with those reported by Pallesen et al who reported an effect of intermittent high intensity training only on the Trail B and not on the Trail A [36].…”
Section: Discussionsupporting
confidence: 92%
“…Although these results are encouraging, there is no clear evidence that HIIT has a superior effect on cognitive function compared to MICE [16]. Recently, original studies have provided more responses with null [31,32] or positive results [33][34][35][36][37] in animal and human studies. Among the studies that achieved positive results, they only compared HIIT to active controls, and as such, the effects of exercise intensity per se were not examined.…”
Section: Introductionmentioning
confidence: 99%
“…Mūsų tyrimo rezultatai parodė, kad pagėrėja tiriamųjų dėmesys ir kognityvinis lankstumas, bet darbinė atmintis lieka nepaveikta. Ankstesniu tyrimu nustatyta, kad taikant didesnį nei 70% intensyvumo aerobinį krūvį 4 savaites po 50 minučių per dieną pagerėja ne tik dėmesys, bet ir darbinė atmintis (Pallesen et al, 2019). Taigi mūsų tyrimo metu tiriamųjų darbinė atmintis galėjo nepagerėti dėl per mažos aerobinių pratimų taikymo trukmės ir per mažo krūvio intensyvumo.…”
Section: Rezultatų Aptarimasunclassified
“…These previous findings provide some rationale to test the hypothesis that HIIT may provide an optimal strategy to enhance cognitive function in older adults. Recently, animal and human studies have provided findings with either null [24,25] or positive effects of HIIT on cognition [26][27][28][29][30][31]. Furthermore, Kovacevic et al [27] found that 12 weeks of HIIT had a greater impact on cognitive function (e.g., working memory) than moderate-intensity continuous exercise in older adults.…”
Section: Introductionmentioning
confidence: 99%